Legal Protection For Consumers Of Refill Drinking Water In The City Of Ternate - Rusdin Alauddin; Irham Rosyidi; Mardania Gazali (IHSA Institute, 2022)
This study aims to (1) determine the legal protection of consumers who are harmed by consuming refilled drinking water. (2) knowing the form of supervision of the relevant agencies on refill drinking water produced by refill drinking water entrepreneurs. The type of research used is juridical, a form of legal research that takes sources from library materials. However, to support the juridical research, an empirical type of research is also needed to determine how to implement the management of Drinking Water Depots. The results of this study indicate that so far, the efforts of refilling drinking water consumers in Ternate City to obtain their rights as consumers have not been maximized. This is because not many people are aware of the Consumer Protection Act. Likewise, with refill drinking, water business actors in Ternate City, not all refill drinking water depots have permits or have registered their businesses with the relevant agencies. Whereas all matters relating to drinking water depots, including the conditions for their establishment, are explicitly regulated in the Decree of the Minister of Industry and Trade Number 651/MPP/Kep/10/2004 concerning Technical Requirements for Drinking Water Depots and their Trade. The supervision of the relevant agencies on refilling drinking water produced by refilled water entrepreneurs is also not running as it should. This is due to the lack of human resources.